THE VALUE OF LANGUAGE POLITENESS IN THE EDUCATION - Hermawati Syarif (International Conference on Languages and Arts, 2014)
The paper discusses how the ethics of language used in communication becomes deficit in educational interaction of student-teacher during educational process. The time changes and the value follow the changes. That is what happens in the social life. The language used by students has nearly broken the norms of politeness strategies. The global era, in which everybody involves in the display of any kind of commercials and action from visual media; the parents do not really care about being together in the family to form heart by heart communication; and the teachers are busy with overload jobs, is assummed to be the causes. Thus, providing students with more language instructional activities related to the discourse of language politeness strategies should be seriously considered in constructing language educational instruction as the part of character buildings. Key Words:   language politeness, deficit, communication in education, character